Pemanfaatan Limbah Pucuk Tebu sebagai Sumber Selulosa Bahan Baku Plastik Biodegradable - Eva Agustina; Risa Purnamasari; Nasrul Fuad Erfansyah; Funsu Andiarna; Nova Lusiana; Irul Hidayati (Biotropic : The Journal of Tropical Biology, 2024)
Plastic waste continues to be a significant environmental issue due to the extended degradation period it requires. Bioplastics represent an innovation in the conventional plastic cycle, being made from natural materials such as agricultural waste containing cellulose. The objective of this research is to determine the influence of adding cellulose from sugarcane tops in the production of biodegradable plastic. The research method begins with the extraction of cellulose from sugarcane tops, including preparation stages, wax removal, bleaching, hemicellulose removal, and delignification. Sugarcane top cellulose is utilized as a raw material for bioplastic. Cellulose with concentrations of 0%, 10%, 30%, and 50% by weight is processed together with a mixture of water and tapioca, to which chitosan and glycerol are subsequently added. Observation parameters for the bioplastic include functional group characterization and mechanical tests, encompassing transparency, tensile strength, elongation, density, thickness, water absorption, and biodegradability. The research results indicate that the characterization of functional groups using FTIR produces spectra of O-H, C-H, C=C, C-O, indicating the constituent components of cellulose, glycerol, and chitosan. Meanwhile, based on the mechanical tests, the 50% sugarcane top bioplastic is the most favorable, with transparency value of 89% transmittance, tensile strength of 39.2 MPa, elongation percentage of 17.32%, density of 0.8444 g/cm3, thickness of 0.276 mm, water absorption of 98.36%, and biodegradability over 4 days. Based on the mechanical tests, the produced bioplastic holds potential for food packaging material.